INDONESIA'S DIPLOMACY STRATEGY ON FOOD SECURITY DURING THE COVID-19 PANDEMIC - Achmad Ismail; Faizul Ibad; Fadhil Muhammad Perdanakusuma; Dimas Giri Gahana (Pojok Publisher, 2025)
Food security is essential for every country to achieve food self-sufficiency. A world filled with news and issues of climate change has led countries to prioritize their national interests, including in the context of food. The purpose of this study is to describe the food diplomacy strategy implemented by Indonesia and Japan in addressing food security issues in 2020. The method used is a qualitative method with a narrative and descriptive analytical approach. This study describes Indonesia's strategy in its cooperative relationship with Japan to improve Indonesia's food security in 2020. The results of this study indicate that in 2020, coinciding with the COVID-19 pandemic, food security issues arose. The Food and Agriculture Organization (FAO) has conveyed the threat of food scarcity during that period. In facing the COVID-19 pandemic, Indonesia is striving to stabilize the economy, one of which is by establishing international cooperation, namely cooperation with Japan.